(untitled) (Research, Society and Development, 2022)
This study determined whether supplementing the diet of laying hens in the final third of laying with vitamin D improves bird health and egg performance and quality. The hens were separated into four groups with six repetitions each and five animals per repetition to test three doses of vitamin D supplementation (50, 100, and 150 mg/kg). The vitamin D supplementation had no effect on the hens performance; however, when we individually evaluated each repetition, we found that the birds of T100 and T150 showed significant increases (P<0.001) in the percentage of the laying rate. Regarding egg quality, the T150 group presented a better result of shell resistance, and the T150 I had a better range of colors and color "a". The yolk percentage was higher in the supplemented groups than the control (T0). On day 21, serum cholesterol levels were lower in supplemented birds groups than in control. At 42 days, the highest vitamin D supplementation for T150 birds resulted in a higher serum albumin concentration, whereas birds in the T100 group had a higher protein concentration. The supplementation had positive and timely effects on the birds’ metabolism, reflected in the higher laying rate and the better egg quality.